Pengaruh Customer Satisfaction Terhadap Financial Performance Melalui Customer Loyalty dan Customer Advocacy Pada Perusahaan Berbagai Sektor di Indonesia - Fanny - Sutjiono; Josua - Tarigan (Business Accounting Review, 2016)
Free trade era makes every companies create and improve their excellence in order to compete with the competitors to attract customers’ heart. Satisfaction and loyalty are powerful keys for the companies to survive because they are important indicators of the company's non-financial performance. The non-financial aspects are useful in the assessment of the performance of the market because it has a strong relationship with the financial performance. Beside that, the level of customer advocacy also has a strong relationship with the financial performance. Advocacy itself is a special form of customer service where companies focus on what is best for the customers. The purpose of this research is to determine the impact of customer satisfaction to financial performance through customer loyalty and customer advocacy in various sectors companies in Indonesia. This research using quantitative approach. The samples are various sectors companies in Indonesia with criteria listed in the Indonesia Stock Exchange, published annual financial report in 2011-2014, and its brand is registered in Indonesia Original Brands (IOB) in SWA magazine and still exist in 2011-2014. The number of companies that fulfil the criteria are 13 companies with a 4-year research period, so the number of research sample is 52 samples. The analysis technique using Partial Least Square (PLS) approach. The results showed a positive impact of customer satisfaction to customer loyalty, customer advocacy, and financial performance. While customer loyalty and customer advocacy has no impact to financial performance, but customer loyalty has positive impact to customer advocacy.